2017
DOI: 10.1002/1873-3468.12705
|View full text |Cite
|
Sign up to set email alerts
|

Translation‐dependent mRNA cleavage by YhaV in Escherichia coli

Abstract: Many bacteria have toxin–antitoxin (TA) systems, where toxin gene expression inhibits their own cell growth. mRNA is one of the well‐known targets of the toxins in the type II toxin–antitoxin systems. Here, we examined the ribosome dependency of the endoribonuclease activity of YhaV, one of the toxins in type II TA systems, on mRNA in vitro and in vivo. A polysome profiling assay revealed that YhaV is bound to the 70S ribosomes and 50S ribosomal subunits. Moreover, we found that while YhaV cleaves ompF and lpp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Varying strains of E. coli (BW25113ΔprlFyhaV, DH5αΔprlFyhaV, and BL21(DE3)ΔprlFyhaV) were used in this analysis [23]. Various versions of YhaV (yhaVΔ241-465, Δ271-465, Δ301-465, Δ331-465, Δ361-465, Δ391-465, Δ406-465, Δ421-465, Δ436-465, or Δ451-465) were amplified by PCR using pBAD24-yhaV as the template with the primers listed in Table 1.…”
Section: Bacterial Strains Plasmids and Primersmentioning
confidence: 99%
See 1 more Smart Citation
“…Varying strains of E. coli (BW25113ΔprlFyhaV, DH5αΔprlFyhaV, and BL21(DE3)ΔprlFyhaV) were used in this analysis [23]. Various versions of YhaV (yhaVΔ241-465, Δ271-465, Δ301-465, Δ331-465, Δ361-465, Δ391-465, Δ406-465, Δ421-465, Δ436-465, or Δ451-465) were amplified by PCR using pBAD24-yhaV as the template with the primers listed in Table 1.…”
Section: Bacterial Strains Plasmids and Primersmentioning
confidence: 99%
“…Previously, PrlF-YhaV was classified as a type II TA system, based in part on homology to the ribosomedependent YoeB and RelE families [22]. Ribosome profiling analysis of the toxin YhaV revealed that the expressed toxin YhaV bound to the 50S ribosomal subunit and inhibited bacterial growth [23]. The RelE toxin is a well-known global inhibitor of translation, and structural analysis suggests that the active site of RelE toxin is located in the C-terminal amino acid region [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Aliquots of fresh medium were inoculated with E. coli 3D8scFv or with the control strain, and the OD 600 and the number of CFUs in the inoculated cultures were measured. Aliquots of the cell cultures were collected at the same time intervals (0 h, 1 h, 3 h, 6 h, 9 h, 12 h, 1 d, 3 d, 6 d, 15 d, 18 d, and 21 d) used for the collection of stools in mice, and the OD 600 and CFU of the cell culture aliquots were measured (Choi et al, 2017). The OD 600 values of the E. coli 3D8scFv culture samples were measured and normalized to the blank value ( Fig.…”
Section: Effect Of 3d8 Scfv On E Coli 3d8scfv Cell Growthmentioning
confidence: 99%
“…Most bacteria have the toxin-antitoxin (Ta) system which is a mechanism to control the cell growth. Toxin induces cell growth arrest and even cause cell death without the co-expression their cognate antitoxins 13,14 . Thus, virus proteases have been considered ideal drug targets.…”
Section: Introductionmentioning
confidence: 99%